Barriers to HIV care and adherence for young people living with HIV in Zambia and mHealth - St Clair-Sullivan, Natalie (Mhealth, 2019)
BACKGROUND: The control of HIV/AIDS has been a contemporary public health success story however, whilst infection rates are falling and people are living longer due to antiretroviral therapy, adolescents and young people remain disproportionally affected. Infection rates and AIDS-related deaths continue to increase in these age groups in some areas globally. This has been primarily attributed to structural barriers including HIV-services not being youth friendly with opening hours conflicting with school time, fears around unintended disclosure and confidentiality, and the attitudes of healthcare professionals—but research targeting these specific age groups remains limited. Early mHealth (i.e., the use of mobile and wireless devices to assist in achieving health objectives) projects have been shown to improve health outcomes in other disease areas and health settings however, amongst people living with HIV, current research is limited. The aim of this study was to explore barriers to HIV care and the acceptability and feasibility of using mHealth to improve retention into care and ART adherence for young people living with HIV (16–24 years old) in Lusaka, Zambia. METHODS: Qualitative in-depth interviews and focus group discussions were carried out in four CIDRZ-supported health facilities in Lusaka, Zambia. Six interviews were carried out with nurses and peer-support workers working with young people living with HIV and three focus groups with a total of 24 young people. Recruitment was via purposive sampling. Interviews and focus groups were recorded, translated and transcribed and entered into NVivo for thematic analysis. RESULTS: Twenty-four of the young persons interviewed had access to mobile phones and reported using them for social networking, information gathering and regular communication. Barriers to HIV care and adherence were largely underpinned by stigma. Participants described healthcare facilities as not being conducive for confidentiality and therefore were reluctant to be seen attending or collecting medication from the pharmacy due to possible unintended disclosure and consequential HIV-related stigma. Clinic opening and waiting times and experiences with healthcare professionals also served as barriers. It was felt unanimously by participants that mHealth would be beneficial in improving retention into care and ART adherence in young people living with HIV. CONCLUSIONS: HIV-related stigma remains a barrier to care. With growing access to mobile phones and internet, and a growing population of adolescents who are already using their phones to support each other and seek information, mHealth appears to be both a feasible and acceptable tool to support retention, provide young people with information, and potentially reduce time spent at health facilities via appointment reminders and electronic drug refill requests.